Besarnya Head Losses Pada Aliran Perpipaan Dari Boiler Feed Water Pump Menuju Boiler di PT. Z - Manahan Hutagalung; Jhon Wira Wahyu Aritonang (CV MEDAN TEKNO SOLUSI, 2023)
The research object observed is the amount of head loss that occurs in the boiler feed water pump when pumping feed water for the boiler, head loss is a flow loss consisting of friction loss head in the pipes, and head loss in bends, reducers, valves, and so on. Head loss is divided into two, namely major head loss and minor head loss. The flow loss due to friction is also known as the major energy loss. Major head loss occurs due to the viscosity of the liquid and turbulence due to the hardness of the pipe boundary wall which will cause frictional forces which will cause loss of flow along the pipe. Minor losses are pressure loss due to friction that occurs in valves, T junctions, joints and cross sections that are not constant. This study aims to determine the magnitude of the major head loss and minor head loss that occurs in the boiler feed water pump and to determine the capacity of the boiler feed water pump after the head loss occurs. From the results of the study it can be concluded that the major head loss is 1.63 m and the major head loss minor is 0.74 m and the pump capacity after head loss is 53.81 m3/hour.